2011
DOI: 10.1111/j.1875-595x.2011.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for the use of silver nanoparticles in dental practice

Abstract: Nanotechnology has been used for medical applications in several forms, including dental practice with the development of silver nanoparticles (Ag NPs) as a useful tool. The aim of this review was to identify the properties and appliances of Ag NPs in dental practice. Silver compounds and NPs have already been used as dental restorative material, endodontic retrofill cements, dental implants and caries inhibitory solution. Despite the effectiveness that Ag NPs has shown in dental practice, Ag NPs remain a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(81 citation statements)
references
References 36 publications
2
68
0
7
Order By: Relevance
“…More recently, the use of AgNPs has been suggested for coating medical titanium implants (Alviano et al, 2005;Huang et al, 2012;Lu et al, 2011;García-Contreras et al, 2011) in the hope of inhibiting biofilm formation and thereby reducing the incidence of microbial infections and rejection.…”
mentioning
confidence: 99%
“…More recently, the use of AgNPs has been suggested for coating medical titanium implants (Alviano et al, 2005;Huang et al, 2012;Lu et al, 2011;García-Contreras et al, 2011) in the hope of inhibiting biofilm formation and thereby reducing the incidence of microbial infections and rejection.…”
mentioning
confidence: 99%
“…Therefore, the next challenge for the dental implantology is an indication of materials, which will limit the risk of colonization with pathogenic microorganisms. Due to proven antibacterial properties Ag nanoparticles are intensively investigated as a material used in dental applications, mainly as dental fillings or implants [28,29]. Strong antibacterial features of Ag are associated with the ability of this metal to interact with sulfhydryl groups of proteins as well as with DNA [30].…”
Section: Discussionmentioning
confidence: 99%
“…Studies analyzing AgNP antimicrobial activity have shown effectiveness against Gram-negative and Grampositive microorganisms (20); however, its main mechanism of action is not fully understood (14). They have been associated with increased adherence to bacterial cell wall, increasing membrane permeability and subsequently bacterial death (17,21). AgNP enhance the release of silver ions, affecting the bacterial respiratory chain because of reactive oxygen species (ROS) and reactive nitrogen species (RNS) production (22,23) which leads to cell damage and finally apoptosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Their antibacterial activity is a result of their cationic nature and high surface density (17,18), with increased interaction with bacterial cells (19). Studies analyzing AgNP antimicrobial activity have shown effectiveness against Gram-negative and Grampositive microorganisms (20); however, its main mechanism of action is not fully understood (14).…”
Section: Introductionmentioning
confidence: 99%